Body Composition and Hydration Status in Young Elderly Women after 6 Weeks' Monavie Juice Supplementation - Ilona Pokora; Ewa Sadowska-Krępa; Izabela Zając-Gawlak; Jana Pelclova (Karolinum Press, 2015)
This study was designed to determine the influence of 6 weeks' MonaVie juice supplementation on body composition and hydration status in young elderly physically active women. Sixteen women, students of University of Third Age, were recruited for this study. All women were physically active (daily energy expenditure 1681.8 ± 297.6 kcal/d). Women were divided into 2 groups: 8 of them applied a supplement MonaVie juice (100 ml/d) (S) for 6 weeks, while the eight other women were allocated to the control group (C). There were measured: BW, Fat%, TBW, Hb, HCT and erythrocyte indices: RBC, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC). Based on Hb and HCT were calculated changes: blood (del BV%), plasma (del PV%) and cell (del CV%) volumes in C and S group. Before experiment all body components and hematologic indices were similar in C and S group. After 6 weeks of MonaVie supplementation no significant changes in body composition but significant decrease: (MCH), (MCHC) and an increase cell volume CV% + 2.89 ± 1.24% were found. In control group after 6 weeks period there were no significant changes in body components and hematological indices. These observations suggest that MonaVie supplementation does not induce significant changes in body composition and hydration status in young elderly women, however causes an increase of cells volume and a decrease of mean corpuscular hemoglobin concentration.